Feasibility of Self-Programming of the Speech Processor Via Remote Assistant Fitting in Experienced Cochlear Implant Users - Paola Angelica Samuel-Sierra; Maria Valéria Schimidt Goffi-Gomez; Ana Tereza de Matos Magalhães; Ricardo Ferreira Bento; Robinson Koji Tsuji (International Archives of Otorhinolaryngology)
Introduction Adults with cochlear implants (CIs) need periodic programming of their speech processors to take advantage of alternative adjustments. However, this requires patients to attend the CI center in person.